Building and Sustaining National ICT Education Agencies : Lessons from Thailand (Schoolnet Thailand) - Rattankhamfu, Saowaruj (World Bank, Washington, DC, 2017)
Thailand's national initiative on ICT usage in schools was launched in 1995 by the country's National Electronics and Computer Technology Center (NECTEC) under the pilot project known as the Thailand School Communication Network (more commonly referred to as 'SchoolNet'). The main objectives of SchoolNet were to network schools inside and outside Bangkok; to connect them to the Internet; and to promote the use of the Internet for teaching and learning in schools. After operating for eight years, the project was transferred from NECTEC to the Ministry of Education (MOE) and served as the foundation for the country's national educational network. Experience from SchoolNet Thailand provides useful lessons related to what can be achieved by small groups with vision and passion; how to operate without dedicated budget allocations from government in the start-up phase; the important role of support from widely respected and influential people outside the particular line ministries in starting something new; how to transition from a small and dynamic pilot initiative into a large government bureaucracy; and the importance of cooperation among related agencies across ministries.